2017
DOI: 10.4172/2329-910x.1000226
|View full text |Cite
|
Sign up to set email alerts
|

Celecoxib 2% Cream in Acute Soft Tissue Injuries: Randomized, Double-blind, Placebo-controlled Clinical Trial

Abstract: Objective: The aim of the study was to evaluate the efficacy of pain reduction and tolerability of topical administration of Celecoxib 2% cream compared to Celecoxib 1% cream and placebo cream in Mexican patients who had acute soft tissue injury in lower limbs. Methods:A randomized, double-blind, placebo control trial with 3 parallel groups was conducted. We include Mexicans patients older than 18 years with diagnosis of acute soft tissue injury in lower limbs. They were randomly assigned to Celecoxib 2% cream… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 21 publications
1
1
0
Order By: Relevance
“…Firstly, we demonstrated that COX-2 and TGF Beta-1 showed similar cellular profiles as both were expressed mainly by the infiltrating inflammatory cells in the wound area, this was in line with other studies [52][53][54][55], however, we endorsed our finding by showing for the first time actual colocalization of Cox-2 and TGF Beta-1 on the cellular level in the wound area. Secondarily, demonstrating that both mediators showed a similar pattern of expression in the wound, where COX-2 upregulation and downregulation was associated with a concomitant similar change in TGF Beta-1, this was in line with other studies in different animal models of inflammation [61][62][63][64][65][66][67][68][69][70]. Thirdly, we endorsed this COX-2 and TGF Beta-1 coordinated relation results further by a correlation studies that showed for the first time a strong correlation between COX-2 and TGF Beta-1 in dermal wounds.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Firstly, we demonstrated that COX-2 and TGF Beta-1 showed similar cellular profiles as both were expressed mainly by the infiltrating inflammatory cells in the wound area, this was in line with other studies [52][53][54][55], however, we endorsed our finding by showing for the first time actual colocalization of Cox-2 and TGF Beta-1 on the cellular level in the wound area. Secondarily, demonstrating that both mediators showed a similar pattern of expression in the wound, where COX-2 upregulation and downregulation was associated with a concomitant similar change in TGF Beta-1, this was in line with other studies in different animal models of inflammation [61][62][63][64][65][66][67][68][69][70]. Thirdly, we endorsed this COX-2 and TGF Beta-1 coordinated relation results further by a correlation studies that showed for the first time a strong correlation between COX-2 and TGF Beta-1 in dermal wounds.…”
Section: Discussionsupporting
confidence: 72%
“…Inflammatory phase of dermal wound determines the quality of the post wounding scars. While the reduction of inflammatory response with early wound closure achieved by Celecoxib application at early time point could be attributed to its direct anti-inflammatory effect [62][63][64]. The improved scar quality could be attributed to an indirect antifibrotic effect of Celecoxib through reducing wound TGF Beta-1 [61,62] with subsequent reduction in collagen deposition and scar formation [89].…”
Section: Discussionmentioning
confidence: 99%